Pengaruh Senam Ergonomik terhadap Penurunan Tekanan Darah Penderita Hipertensi di Posyandu Tinggede Selatan - Susanto, Denny; Purwiningsih, Sri; Kantohe, Imelda (Yayasan Kawanad, 2025)
Hypertension is one of the non-communicable diseases that often occurs in society and is known as a